The impact of the war in Ukraine on energy policies in Romania and Moldova - Iliaș, N.; Fetiniuc, V.; Radu, S. M.; Iliaș, I. T.; Offenberg, A.; Offenberg, I. (Національний технічний університет "Харківський політехнічний інститут", 2024)
Russia's unjustified war against Ukraine has had a strong impact on energy markets. EU countries closely coordinate their actions to ensure affordable energy supplies and prices. The largest country in the region, Romania has a special relationship with Moldova, including in the energy sector. The Republic of Moldova does not have its own energy resources and is practically completely dependent on imports of fossil fuels and electricity from Ukraine and Romania. Currently, there are regional projects that would ensure Moldova's energy security and resilience to current and future shocks and boost the energy transition. The paper briefly treats the basic elements of the vision «3M - MANAGEMENT» in the form of a concept adaptable to the energy sector in transition, which holistically addresses the three main dimensions of modern management dealing with this type of projects, at micro, median and macro educational level. The authors believe that the development of this holistic concept can generate valuable professionals who, taken over in the political environment, will determine substantial changes in energy policies in the two states and beyond.
Keywords: industrial development channel; commercial channel; social channel; common energy policy channel; educational management channel